Knjiga o transvrsizmu. Suzana Marjanić, Cetera animantia: od etnozoologije do zooetike - Nikolić, Ivana (Anafora, 2023)
Knjiga o transvrsizmu. Suzana Marjanić, Cetera animantia: od etnozoologije do zooetike